Analysis of Stability and Earth Thrust Against Retaining Walls - Jose Medina (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
When a retaining wall moves laterally, the earth pressure decreases on the active side of the wall, and after the maximum friction force is mobilized at the base of the wall, the thrust increases on the passive side. The lateral displacement ends when the balance of forces in the horizontal direction is reached. The theories of Coulomb and Rankine consider that the shear strength of the soil contained by the wall is completely mobilized, but this hypothesis is not fulfilled, since the wall stops when the balance of forces is reached in the horizontal direction, so the earth thrust acting on the active side is greater than the active thrust calculated with Coulomb and Rankine theories, therefore, an error is incurred, that is on the side of insecurity. In this article based on Coulomb’s theory a method is presented to calculate the earth thrust on the active side of the wall considering the safety factors which the wall is designed. After the earth thrust on the active side is obtained, the earth thrust on the passive side is obtained from the balance of forces in the horizontal direction. A practical example is presented, where the traditional methodology is compared with the one stated here, where the differences are important, and they are on the side of insecurity. With the traditional methodology the wall does not detach from the base, while with the one exposed here the wall detaches from the base.